2008
DOI: 10.1158/1078-0432.ccr-07-1634
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Transforming Growth Factor β Receptor Kinase Inhibitor, A-77, Prevents the Peritoneal Dissemination of Scirrhous Gastric Carcinoma

Abstract: Purpose: Transforming growth factor h receptor (TGFh-R) is reported to correlate with the malignant potential of scirrhous gastric carcinoma. The aim of the current study is to clarify the possibility of molecular target therapy with a TGFh-R inhibitor, A-77, for the treatment of peritoneal dissemination of scirrhous gastric cancer. Experimental Design: Three scirrhous gastric cancer cell lines and two fibroblasts were used. For in vivo experiments, the A-77 was administered i.p. to mouse models of peritoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…In the present study, we established a peritoneal carcinomatosis model by using human scirrhous gastric cancer cell line OCUM2MD3. It was previously reported that these cells, intraperitoneally inoculaed, had developed peritoneal metastasis accompanied by stromal fibrosis of the peritoneum in nude mice (22,23). The result of our in vivo study supports the assumption that AT1 receptor blockade therapy provides a new strategy for peritoneal carcinomatosis through suppression of both tumor growth and stromal fibrosis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, we established a peritoneal carcinomatosis model by using human scirrhous gastric cancer cell line OCUM2MD3. It was previously reported that these cells, intraperitoneally inoculaed, had developed peritoneal metastasis accompanied by stromal fibrosis of the peritoneum in nude mice (22,23). The result of our in vivo study supports the assumption that AT1 receptor blockade therapy provides a new strategy for peritoneal carcinomatosis through suppression of both tumor growth and stromal fibrosis.…”
Section: Discussionsupporting
confidence: 88%
“…The gastric cancer cell lines used in this study were human gastric cancer cell line, OCUM2MD3 which was kindly supplied by Department of Surgical Oncology, Osaka City University Graduate School of Medicine, Osaka, Japan, and MKN28, AZ521, TMK1, MKN45 which were purchased from American Type Culture Collection (Rockville, MD, USA). OUUM2MD3 is a human scirrhous gastric cancer cell line and it has a strong ability to metastasize into the peritoneum in nude mice (22,23). This cell line was maintained in Dulbecco's modified Eagle's medium (DMEM; Gibco-BRL, USA) supplemented with 10% fetal bovine serum (FBS; Iwaki, Japan), 2 mM glutamine (Nissui Pharmaceutical, Tokyo, Japan), 10 U/ml penicillin-streptomycin (Gibco-BRL) and the other cell lines were maintained in RPMI-1640 medium (Nissui Pharmaceutical) supplemented with the same chemicals.…”
Section: Methodsmentioning
confidence: 99%
“…The attachment of GC cells to the peritoneum is an important step in the initial phases of metastatic dissemination (10)(11)(12). The results of the present study showed that only a small subset of GC cells have potential metastatic ability in the peritoneum.…”
Section: Discussionsupporting
confidence: 47%
“…In this same study, patients with high levels of ␣5-integrin died 9 months earlier than those displaying low ␣5-integrin expression. 33 Following a similar rational, Kawajiri et al 34 recently showed that the transforming growth factor-␤-R inhibitor, A-77, decreased the adhesive and invasive abilities of diffuse gastric cancer cells to the mice peritoneum, as well as the size and number of metastatic nodes, and demonstrated that this effect was mediated by decreased expression of integrins.…”
Section: Discussionmentioning
confidence: 87%